The Monophthongs of Traditional Cockney and Popular London Speech in Context (Philologia, 2021)
The paper examines the pure vowels of Traditional Cockney as pronounced in connected speech by three elderly male speakers and compares the F1 and F2 values with those obtained for RP by Deterding, and those from a previous experiment with the same speakers for the vowels in citation form (in the context /h_d/).
Keywords: Cockney; English dialectology; English pure vowels; English sociolinguistics; Popular London speech